Evaluation of the variations and potential clinical use of second trimester serum markers for the detection of pre-eclampsia - Gautam, Savita S.; Kaur, Manmeet; Chaudhary, Naimaa K.; Sharma, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In many areas of world, hypertensive disease in pregnancy is the single most common cause of maternal death. Pregnancy associated hypertension remains unsolved despite decades of intensive research and remains the most significant problem in obstetrics. The aim of present study is to evaluate the variations and potential clinical use of second trimester serum markers for the detection of pre-eclampsia. Methods: In an observational study, estimations of serum of human chorionic gonadotropin (β-hCG) were done in 347 randomly selected women at 13-20 weeks of gestation in august 2015 to may 2016. Multiple of median (MOM) was calculated from charts of norms available for that weeks of pregnancy. The subjects were followed up till delivery for the development of hypertension in pregnancy and results analysed statistically with Chi-square test. Results: Out of 347, 47 women developed hypertyension and 2MOM of β hCG was significantly (P<0.001) elevated in those who developed hypertension compared to normotensive women. In our study group a significant associations between elevations in second trimester β-hCG and development of hypertension was observed. Thus with second trimester serum marker study, prediction of pre- eclampsia is possible at incipient stage and adverse pregnancy outcome can be minimized. Conclusions: Maternal serum β-hCG level was found to be significantly higher in hypertensive group than normal group.